Ocean Acidification Mitigates the Negative Effects of Increased Sea Temperatures on the Biomineralization and Crystalline Ultrastructure of Mytilus - Knights, Antony M.; Norton, Matthew J.; Lemasson, Anaëlle J.; Stephen, Natasha (Frontiers in Marine Science, 2020)
Negative impacts of global climate change are predicted for a range of taxa. Projections predict marked increases in sea surface temperatures and ocean acidification (OA), arguably placing calcifying organisms at most risk. While detrimental impacts of environmental change on the growth and ultrastructure of bivalve mollusc shells have been shown, rapid and diel fluctuations in pH typical of coastal systems are often not considered. Mytilus edulis, an economically important marine calcifier vulnerable to climate change, were exposed to current and future ocean acidification (380 ppm and 1000 ppm pCO2), warming (17°C; 20°C), and ocean acidification and warming (OAW) scenarios in a seawater system incorporating natural fluctuations in pH. Both macroscopic morphometrics (length, width, height, volume) and microscopic changes in the crystalline structure of shells (ultrastructure) using electron backscatter diffraction (EBSD) were measured over time. Increases in seawater temperature and OAW scenarios led to increased and decreased shell growth respectively and on marginal changes in cavity volumes. Shell crystal matrices became disordered shifting toward preferred alignment under elevated temperatures indicating restricted growth, whereas Mytilus grown under OAW scenarios maintained single crystal fabrics suggesting OA may ameliorate some of the negative consequences of temperature increases. However, both elevated temperature and OAW led to significant increases in crystal size (grain area and diameter) and misorientation frequencies, suggesting a propensity toward increased shell brittleness. Results suggest adult Mytilus may become more susceptible to biological determinants of survival in the future, altering ecosystem structure and functioning.